Side-Chain Liquid Crystal Conducting Polymers. (September 2016) - Roudini, Danesh; Foot, Peter J.S.
This article overviews some of the research progress on the effects of incorporating liquid crystalline functionalities into commercial conjugated polymers such as polythiophene, polypyrrole and polyaniline. Polarisable aromatic mesogens are generally attached via a flexible spacer group to the monomers to form a side-chain. Consequently, the self-organising properties of liquid crystals can be used to influence the conducting polymer backbone and control the electrical, magnetic and mechanical properties of the material. Some applications of these interesting materials are discussed.